Integrasi Filosofi Adat Kneter-Ktaek dalam Pembelajaran Sejarah di Perbatasan Indonesia-Timor Leste - Yohanis Kristianus Tampani (STIKes Ibnu Sina Ajibarang, 2023)
Integration of the Kneter-Ktaek Indigenous Philosophy in Learning History at the Indonesia-Timor Leste Border The method in this research is a qualitative approach with the library study method, namely collecting or conducting document studies on sources and literature related to this study. The results of this study indicate that learning has a similar meaning to teaching, although it has a different connotation. In the context of education, teachers teach so that students can learn and master the content of lessons so as to achieve something objective (cognitive aspect) can also influence changes in attitudes (affective aspects) and acquire certain skills (psychomotor aspects). The purpose of learning history is not just to memorize and repeat event information. More than that, the intended purpose is for students to actualize themselves in society as social beings. There are three main points divided into categories. First, Hakneter-Haktaek (Appreciation and Respect). Second, Ktuik-Kbatak/Kadalolok (Boundaries). Third, So Re (Dignity). To uphold So Re (dignity and dignity) in public life is known. First, Sara Mata-Didin Sara, which is a principle of respect for mutual respect (hatetu-harani). Second, Sara Mata-Soe Re. Third, Lia Lulik.